A path to recovery for overlooked populations and their unique challenges: integrating rehabilitation in palliative care for patients with substance use disorders - Aljassem, Annas; Spickler, Michael; Kapur, Nandita (Frontiers in Rehabilitation Sciences, 2024)
Palliative care is a growing medical specialty focusing on providing compassionate and holistic management for those facing life-threatening diseases. These patients frequently present with physical, functional, emotional, and psychosocial problems that require comprehensive interdisciplinary management. However, there is a substantial opportunity to improve care for patients in palliative care who also have a substance use disorder (SUD). These opportunities include direct provision of SUD treatments by specialist palliative care providers and the integration of physical medicine and rehabilitation services. The purpose of this article is to examine the misunderstood and underutilized interaction between palliative care and SUDs, as well as describing the unique opportunities provided by physical medicine and rehabilitation providers to achieve a patient's palliative care goals and optimize overall quality of life. Substance Use Disorder is a chronic, often relapsing, illness that is relevant to palliative care practice due to the potential for significant morbidity and mortality through organ failure, chronic infections, and overdose syndromes. In traditional palliative care practice, it has been observed that past or current SUD diagnoses are often left untreated, resulting in increased distress, and exacerbating an already complex medical situation. Furthermore, many of these patients also experience physical, functional, or psychosocial changes that, when left untreated, will worsen distress and quality of life. To provide more comprehensive and successful palliative care for patients with SUD, the authors recommend an increased emphasis on specialist palliative care training in SUD management, proactive integration of rehabilitation services into the palliative care team, and consistent advocacy for these steps in various arenas. Combined, these actions can improve the care team's ability to provide a holistic, patient-centered approach that can have substantial positive outcomes for patients, health systems, and society.